Case report: post esophagectomy esophageal reconstruction in esophageal injury due to caustic materials - Danardono, Edwin (Folia Medica Indonesiana, 2017)
The esophageal caustic injury is rare, but it requires precise and complex management. A variety of reconstruction techniques have been done, but despite the increasing volume, the incidence of complications is still relatively high. We reported the experience in our center in handling esophageal reconstruction in patients with caustic esophageal injury that caused oesophageal stricture between 2014-2017. This study used case series method with literature review. The results showed that between 2014-2017, there were 3 patients with caustic esophageal injury. All patients undergoing esophageal reconstruction surgery were included under conditions of malnutrition. Two were caused by HCl and the rest by NaOH. All patients underwent a resection of stricture segment of the esophagus, either using partial or total esophagectomy. Anastomosis leakage occurred in all cases, but improved with conservative treatment. The average length of hospitalization was 27 days. The intraoperative blood loss in patients ranged from 450-700 cc. In conclusion, proper preliminary management can provide approppiate preparation of the patients for definitive or reconstructive surgery, especially to avoid malnutrition. The ideal reconstruction still could not be established, and the rate of postoperative complications was still high. The length of patient hospitalization was also relatively long.